Ambient Media on The Behavior of the 5M Movement Disciplined in Eco-tourism Wonorejo Mangrove Surabaya - Aileena Solicitor Costa Rica El Chidtian; Diana Aqidatun Nisa; Riza Septriani Dewi (Future Science, 2021)
The COVID-19 pandemic in Indonesia has not yet ended. In fact, the situation is getting worse with many people being exposed, millions of people are confirmed positive for COVID-19 and it continues to grow every day, both from medical personnel, state civil apparatus and other public services. As an effort to prevent the spread and exposure of COVID-19, the Government of Indonesia has issued policies to stop the rate of increase in Covid-19 cases, one of which is the policy of making a health protocol for the 5M movement (Washing hand, Wearing Mask, physical distancing, Avoiding crowds and Reducing mobility). However, there are still many people who do not comply with the health protocol. This can be found in tourist sites, such as the Wonorejo Mangrove Ecotourism. To assist the government in suppressing the rate of increase in Covid-19 cases, it takes a unique and unusual media in conveying the importance of disciplined behavior in implementing 5M, one of which is through ambient media design. Ambient media is considered an effective medium to convey the message of the importance of disciplined behavior in implementing 5M and is then expected to contribute positively to the development of similar tourist areas. For this reason, research is carried out on the design of ambient media that is attractive to the public, especially tourist visitors. The results of this study are expected to produce ambient media that can attract the public so that education about the importance of disciplined behavior in implementing 5M can be carried out effectively. The method used is a qualitative research method. The data is obtained in non-numbers, but it could be in text, documents, pictures, photos, artefacts, or other objects found during the research. The research process includes the collection of primary and secondary data. Primary data consists of observation, documentation and semi-structured interviews with tourist visitors, while secondary data uses references and literature. The final result of the research is to produce ambient media that can convey messages to the public about the importance of disciplined behavior in implementing 5M effectively.